Does Good Governance Affect Globalization? A case of Bangladesh - Md. Monirul Islam (Universitas Sultan Ageng Tirtayasa, 2019)
Development, in part, depends on the institutional quality of a state administration (good governance) to respond to the external affair (globalization). To corroborate it, the study aims to investigate the effect of good governance on globalization by employing both Auto Regressive Distributive Lag (ARDL) and VAR-based Variance Decomposition (VDC) estimation techniques in the context of Bangladesh over the period 1990-2016. In addition, almost similar result is found in this nexus while using both two techniques—ARDL and VDC. The study finds that there appears a co-integration between good governance and globalization in which ‘voice and accountability’ affects globalization significantly both in the long and short run. ‘Political stability and no violence’ has significantly negative impact both in the long and short run. Besides, government effectiveness, rule of law, regulatory quality and control of corruption have no substantial impact on globalization in both long and short run. Therefore, the study suggests taking appropriate policy measures to galvanize the core governance/good governance mechanisms to reach the aspired trajectory of globalization.